Status of Mn, Fe, Cu, Zn, B and Mo in Rift Valley Soils of Ethiopia: Laboratory Assessment - Baissa, Teklu; Suwanarit, Amnat; Osotsapar, Yongyuth; Sarobol, Ed (Agriculture and Natural Resources, 2007)
Forty soil samples at a depth of 0-15 cm were collected from Andisols of Ethiopian Rift Valley following two moisture regimes and two farming practices. The objectives of the study were to assess the status of manganese (Mn), iron (Fe), copper (Cu), zinc (Zn), boron (B) and molybdenum (Mo) in the soils and to examine effects of moisture and farming practices on the nutrients. The status of Mn, Fe, Cu and Zn were determined using diethylene triamine pentaacetic acid-triethanolamine (DTPA-TEA), ammonium bicarbonate diethylene triamine pentaacetic acid (AB-DTPA) and Mehlich III methods using atomic absorption spectrophotometer. Boron was analyzed by hot water extraction method and Mo by ammonium acetate etheline diamine tretaacitic acid (EDTA) extraction method using spectrophotometer. The status of Mn, Zn and B were in the sufficient range in all of the samples. The status of Fe and Mo were in the sufficient ranges, except for 7.5% and 40% of the samples, respectively. In Vitric Andisols the status of Cu in all the samples were in the deficient ranges in traditional farms using DTPA-TEA method, while the samples were in sufficient ranges using AB-DTPA and Mehlich III methods in intensive farms. In Mollic Andisols the status of copper of most of the samples in both farming practices were in the deficient range. The status of Mn was mostly higher in traditional farms than in intensive farms in Vitric and Mollic Andisols. In Vitric Andisols the contents of Fe, Cu, Zn, B and Mo were higher in intensive farms than in traditional farms. In Mollic Andisols the contents of Fe, Cu and Zn were higher in traditional farms than in intensive ones, while B and Mo were higher in intensive farms than in traditional farms.